Gold(I)-catalyzed hydroaminaloxylation and petasis-ferrier rearrangement cascade of aminaloalkynes - Gade, Amol B.; Patil, Nitin T. (Organic Letters, 2016)
An efficient method has been developed to generate a diverse array of indolizidines and quinolizidines from readily available aminaloalkynes via a gold(I)-catalyzed hydroaminaloxylation and Petasis-Ferrier rearrangement cascade. The method enabled a formal synthesis of (+/-)-antofine.